Incidental Durotomy Following Transforaminal Lumbar Interbody Fusion Performed with the Modified Wiltse Approach - Sheinis, Dimitri; Sheinis, Vadim; Benharroch, Daniel; Ohana, Nissim (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Purpose Incidental durotomy is an intraoperative complication that occurs in 3 to 27% of lumbar spine surgeries. It has been reported more commonly following revision spinal procedures.Study Objectives To investigate the frequency of incidental durotomy while performing transforaminal lumbar interbody fusion (TLIF) using the modified Wiltse approach. A secondary goal was to compare the incidence of durotomy in patients undergoing primary spine surgery with those undergoing revision surgery.Methods A group of consecutive patients who had undergone (TLIF) in the last 10 years ending in 2015 were enrolled in the study. All patients underwent TLIF via the modified Wiltse approach that included a central midline skin incision, followed by a paravertebral blunt dissection of the paraspinal muscles to reach the transverse processes. The deep paravertebral dissection was done conservatively, one side at a time. Demographic and clinical data were collected when relevant to the comparison.Results The study cohort encompassed 257 patients: 200 primary cases and 57 revisions. The frequency of incidental durotomy was equal in both groups: 3.5% each (7/200 and 2/57). All durotomies were repaired primarily. No other immediate or late complications were observed during follow-up.Conclusion The present study displays a limited incidence of durotomy in the primary interventions and to a lesser degree in the revisions, all of which had used a TLIF performed with the modified Wiltse approach. This procedure probably circumvented the need for further revisions.
Keywords: spinal surgery; transforaminal lumbar interbody fusion; revision; incidental durotomy